Pemanfaatan Artificial Intelligence Untuk Pemasaran Digital Bagi Kelompok Rumah Usaha Mikro, Kecil, dan Menengah Labuhanbatu - Purnama, Iwan; Syahputra Harahap, Hasmi; Karim, Abdul; Sempurna, Teguh; Marha As, Pawa Niassa (JPM: Jurnal Pengabdian Masyarakat, 2024)
The use of Artificial Intelligence (AI) in digital marketing has become an effective strategy in increasing the competitiveness of small and medium enterprises. This community service activity aims to identify the benefits and implementation of AI in digital marketing strategies for SME house groups in Labuhanbatu. By using AI technology, SMEs can increase marketing efficiency, target consumers more precisely, and optimize promotional costs. This study uses a qualitative descriptive method, by collecting data through interviews and observations on SME actors who have adopted AI in their marketing activities. The stages of implementing the community service program are carried out in five core stages, namely: Socialization (Digital Marketing and Cooperatives), Training (Use of Web, GPT Chat and Training in Making Cooperative Formation Documents), Application of Technology (computers, laptops, androids and others), Evaluation Assistance (product monitoring and evaluation and use of AI), and Program Sustainability (Improving good Marketing Results). The results of community service activities show that the use of AI can help SMEs in conducting market segmentation, content personalization, and customer service automation, which overall contribute to increased sales and consumer loyalty. However, challenges such as lack of digital literacy and limited resources are still major obstacles in the optimal implementation of AI. Therefore, regular training and mentoring are needed for UMKM house groups in Labuhanbatu so that they can make maximum use of AI in digital marketing strategies.